Apolipoprotein e gene polymorphisms in essential hypertension: a preliminary study with meta-analysis - Ibrahim, Wisam Nabeel; Ku Zaifah, Norsidah; Draman, Samsul; Abdullah, Nor Zamzila; Mokhtar, Rafidah Hanim; A.Talib, Norlelawati (The Faculty of Medicine, International Islamic University Malaysia, 2015)
Introduction: Essential hypertension is a multifactorial disease. Many experimental studies have elucidated the role of oxidative stress and atherosclerosis in the pathogenesis of essential hypertension. Apolipoprotein E is a plasma protein that is found to have antioxidant properties, and it also protects against atherosclerosis. Interestingly, the biological function of apolipoprotein E is strongly affected by polymorphisms in its gene. Based on this evidence, our aim was to investigate the association of apolipoprotein E gene polymorphisms with essential hypertension. Methods: This study was conducted on 70 hypertensive patients and 73 control participants recruited from the Balok governmental health clinic in Kuantan, Pahang. The polymerase chain reaction restriction fragment length polymorphism assay (PCR-RFLP) was used for determination of the apolipoprotein E genotype. Our results were also verified later by direct sequencing of the amplicons. Results: There was no significant association of apolipoprotein E allele or genotype frequencies with hypertensive disease or blood pressure levels, although the E4 allele was slightly more frequent in the hypertensive patients than in the control group (OR=1.055; 0.471–2.359, CI 95%). To improve the precision of the study and to settle the controversies among similar studies meta-analysis was performed; however it revealed a net nonsignificant